Risco de mercado segundo implementação do acordo de Basiléia no Brasil: uma comparação da abordagem padronizada com métricas de VaR e Stress-Testing - Ferreira, José Augusto Mazzoni Martins (2017)
This work evaluates the regulatory capital required by Brazilian Central Bank (“BCB”) from financial institutions under its regulation, concerning the standard approach for marked risk, compared to alternative approaches commonly used by the financial industry, equivalent to VaR and Stress-Testing models. For a chosen group of risky assets (foreign currencies, stocks, stock indexes, commodities and interest rates), it was calculated the regulatory capital required by BCB under standard approach and compared to the estimated potential losses, according the alternative models. The results evidence a conservative position by BCB related to market risk of foreign currencies and interest rates, being more suitable for commodities and lenient for equities and their respective indexes. It is also possible to observe the existence of regulatory arbitrage, in which there is very low regulatory capital requirement (or no requirement) for certain risky assets portfolios.